2019
DOI: 10.3390/ijerph16234807
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sanitizers on Microbial Levels of Chicken Meat Collected from Commercial Processing Plants

Abstract: Chicken meat can potentially become contaminated with bacteria at the processing plant. In Australia, there is currently a lack of knowledge on the parameters and indications of use of non-chlorine based treatments in the chicken meat processing plants. Chlorine is widely used as a sanitizer in Australian chicken meat processing plants but due to occupational health and safety concerns and consumer perception, there is a need to identify alternative sanitizers. This study aimed to assess the efficacy of four d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
0
23
0
1
Order By: Relevance
“…Studies performed in Australia and Brazil on chicken meat processing plants showed the efficiency of several chemical agents, including sodium hypochlorite, in reducing the microbial load of Salmonella and Campylobacter when used properly [ 32 , 33 ]. The strains identified in our study that were tolerant to different sanitizers suggests the inappropriate use of these agents in the routine of the industrial environment, posing a real risk of resistance and adaptation of these bacteria [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies performed in Australia and Brazil on chicken meat processing plants showed the efficiency of several chemical agents, including sodium hypochlorite, in reducing the microbial load of Salmonella and Campylobacter when used properly [ 32 , 33 ]. The strains identified in our study that were tolerant to different sanitizers suggests the inappropriate use of these agents in the routine of the industrial environment, posing a real risk of resistance and adaptation of these bacteria [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…In some countries, chlorine is often used in chicken meat processing plants with the objective to reduce levels of Campylobacter and Salmonella (Anonymous, 2005;Chousalkar et al, 2019). The MIC experiments revealed that 97.5% of C. jejuni and 92.6% C. coli isolates required chlorine levels higher than 8 ppm to inhibit their growth completely.…”
Section: Discussionmentioning
confidence: 99%
“…The Campylobacter isolates used in this study were isolated during a separate study investigating the efficacy of sanitizers during chicken meat processing (Chousalkar et al, 2019). Briefly, chicken meat carcasses (15 birds from each of eight different broiler production sheds) were collected from two separate processing plants prior to the inside-outside wash step.…”
Section: Isolation Of Campylobactermentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies are located in references (1,2,10,11,12,14,20,24,26,30,31,32,36,37,39,40,41,43,44,46,48,50,56,60,61,62). The publication date ranged from 2004 to 2020, but most of the articles were published from 2013 onwards.…”
Section: Review Methodologymentioning
confidence: 99%